Visual language for the World Wide Web - Honeywill, Paul (Intellect, 1999)
In this digital age, are there cultural lessons for us in looking to the earliest kinds of communications? The icons used in ancient Mayan and Sumerian language systems are presented here as direct cultural links to the visual presentation of World Wide Web pages on the Internet. The book shows how the development of digital screens has caused visual human communication to come full circle from the earliest representations. The in-depth analysis demonstrates how these visual languages now serve as a rich source for renewed study for the development of meaningful computer icons.